Usage of satellites for the Earth remote sensing: legal problems and prospects - M. N. Lysenko; P. N. Lozhkovoi (Правоприменение)
The subject of the study incorporates the problems and prospects of remote sensing of the Earth, an analysis of the effectiveness of the international legal framework in this area is given in the article.General and special methods of legal analysis were used.The main results of the research include the proof that from a technical point of view, the definition and concept of remote sensing do not cause disagreement among professionals, but it was not possible to achieve consensus on the international legal status of remote sensing. It is not in the main sources of international space law. The Principles of Remote Sensing of 1986 are imperfect and outdated in many respects, although they remain the only universal international document regulating remote sensing, and have not been challenged for more than 30 years. A balance has been established between the interests of states on the main controversial issues, such as the relationship between freedom of space monitoring, state sovereignty and access to remote sensing data.The results are practically significant, as they can serve as the basis for new normative legal acts at the international level, in the long term it is important to further expand cooperation in the field of remote sensing within the UN and other international organizations, conclude regional and bilateral agreements and develop national legislation.The conclusion of the study is that the formation of the legal framework for remote sensing occurs by integrating the norms of "soft laws" into national laws, fixing them in international treaties and, as a consequence, the emergence of norms of customary law and norms of international law.